Secularization of the Miracle in Medieval Georgian and European Literature - Nino Chakunashvili (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2011)
Secularization means transfer from the spiritual or ecclesiastical sphere to secular. In the sphere of philosophy and in literary criticism this term is used to refer to conceptualization of a definite manifestation of ecclesiastical thought into secular content. I use this term in this meaning in the present paper that deals with the reflection and meaning of miracle in mediaeval Georgian and European literature. The transformation of miracle in the process of transition from early medieval to late medieval literature takes place along the line of secularization. It comes close to reality, accentuating man’s high, moral, intellectual and physical features. From this point of view, Rustaveli’s “The Man in the Panther Skin” stands at the border of a new period – that of the Renaissance.